(untitled) (GeoPatterns, 2025)
Salt diapirs are geological formations that appear in the subsurface and are formed over millions of years. Such formations occur due to the density difference between the salt and the surrounding rock. The density difference causes the salt to penetrate throughout the strata and, therefore, the salt rises to the surface in a process known as diapirism. The importance of salt domes, structures that form because of diapirism, lies on the fact that due to the impermeability of the salt and the deformation associated with the ascent of these structures, salt domes become excellent oil traps, with important reserves. Therefore, it is important to know the conditions that dominate the development of salt domes as well as their evolution and formation environments. If the subsurface is considered as a continuum and by means of the momentum equations, Newton’s second law and the heat conservation equation, in addition to an Eulerian approach to matter, numerical models showing the evolution of salt domes can be created, and thanks to them, the parameters that influence the formation of the domes can be calculated. In this work it is concluded that some of the parameters that determine the formation and ascent of the diapir are the width and height of the initial Gaussian anomaly, the viscosity of the salt, the temperature, and the thickness of the salt layer.